Wittgenstein's On Certainty: Insight and Method - Brice, Robert Greenleaf (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book considers the important twentieth century Austrian philosopher, Ludwig Wittgenstein, and his conception of certainty. In his work entitled On Certainty, Wittgenstein provides not only a brilliant solution to a previously intractable philosophical problem, but also the elements of an entirely new way of approaching this and similar longstanding, apparently unresolvable, problems. In On Certainty, he re-conceives the problem of radical skepticism-the claim that we can never really be certain of anything except the contents of our own minds-as a kind of philosophical "disease" of thought. His approach to the problem, which is emphasized in the book, is similar to the treatment of disease, has two main goals: (1) bring about an awareness in the philosopher that this kind of extreme skepticism is not a methodological approach to be taken seriously, and, with this awareness, (2) an attempt to replace this radical skepticism with a practical, Common Sense framework. Implicit in Wittgenstein's approach are a number of strategies found in a contemporary approach to psychotherapy known as Cognitive Behavioral Therapy (CBT). These strategies, along with philosophical methods and scientific practices rooted in the Scottish School of Common Sense, seek to diagnose and treat irrational thoughts and beliefs that often emerge (and re-emerge) in the discipline of philosophy. The aim of this book, then, is to provide students of philosophy with the tools necessary to adjust and reshape these irrational, self-defeating thoughts and beliefs into something new, something healthy.
On Certainty: Scholarship, Development, and Placement -- Philosophical Therapy -- Background to On Certainty -- Philosophical Therapy: A Cure for Our "Philosophical Disease" -- Knowledge and Belief -- Language-Game of Knowledge, Hinge-Propositions, & Actional Certitude -- Therapeutic Philosophy: "A Quite Different Method" -- Appendix -- Index.
Keywords: Knowledge, Theory of; Language and languages; Mathematical logic; Metaphysics; Language and languages-Philosophy.; Epistemology; Language History; Mathematical Logic and Foundations; Metaphysics; Philosophy of Language